Numerical Investigation of Conjugated Heat Transfer of the Plate-Type Fuel Assembly in the Research Reactor - Li, Quan; Ma, Qiang; Li, Yuanming; Chen, Ping; Ma, Chao; Zhao, Bo; Chen, Hao (Frontiers in Energy Research, 2021)
In nuclear reactors, the research of conjugated heat transfer between the fuel and coolant in the fuel assembly is fundamental for improving the safety, reliability and economy. The numerical approach based on Computational Fluid Dynamics (CFD) can be used to realize the rapid analysis of the conjugated heat transfer. Besides, the numerical simulation can provide detailed physical fields that are useful for the designing and optimizing of the fuel assembly. The plate-type fuels are generally used to enhance heat transfer in research reactors with high power density. In this study, a standard plate-type fuel assembly in the research reactor was taken into consideration. The solid-fluid conjugated heat transfer of the fuel assembly and coolant was numerically investigated. In the fluid region, the subcooled flow boiling simulation model was established by implementing the Rensselaer Polytechnic Institute model into the Euler multi-phase flow method. The results show that the conjugated heat transfer of the fuel assembly and coolant can be simulated using the model established in this work. The influence of fluid velocity, power density and the width of the flow channel on the temperature distribution and the conjugated heat transfer was investigated and discussed.